Comprehensive Analysis of Ferroptosis- and Immune-Related Signatures to Improve the Prognosis and Diagnosis of Kidney Renal Clear Cell Carcinoma - Xing, Xiao-Liang; Liu, Yan; Liu, Jiheng; Zhou, Huanfa; Zhang, Huirong; Zuo, Qi; Bu, Ping; Duan, Tong; Zhou, Yan; Xiao, Zhiquan (Frontiers in Immunology, 2022)
Background Almost 30% of Kidney renal clear cell carcinoma patients with advanced cancers eventually developed to metastases, and the 5-year survival rate are only nearly 10%. Aberrant DNA methylation is significantly associated with the development of kidney cancers. The aim of our present study was to identify suitable ferroptosis- and immune-related biomarkers correlated with aberrant methylations to improve the prognosis and diagnosis of KIRC. Methods ChAMP and DESeq2 in R were used to screen the differentially expressed probes and differentially expressed genes respectively. Univariate and multivariate Cox regression were used to identify the suitable ferroptosis- and immune-related biomarkers. Results We identified five ferroptosis- and immune-related biomarkers (CCR4, CMTM3, IFITM1, MX2, and NR3C2) were associated with the overall survival of KIRC independently. The areas under the receiver operating characteristic (AUC) value of prognosis model were 0.74, 0.68, and 0.72 in the training, validation, and entire cohorts respectively. The sensitivity and specificity of the diagnosis model were 0.8698 and 0.9722 respectively. The risk value of the prognosis model was actually correlated with several immune cells and factors. Conclusion In the present study, we found five FI-DEGs could use as prognosis and diagnosis biomarkers for KIRC patients which remains further clinical studied.